2019
DOI: 10.17263/jlls.631560
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative inquiry into the application of 9th grade EFL program in terms of the CEFR

Abstract: Current study investigated applicability of the 9 th Grade EFL Program with regard to proficiency descriptors and educational principles of the Common European Framework of Reference for Languages (CEFR). Qualitative inquiry was followed by adopting a phenomenological approach to conduct the study. The data were collected through document analyses, face-to-face interviews, and teacher and students observations regarding classroom instructions. Descriptive analysis was administered to analyze the data obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…In addition, as previously mentioned, the participants were not full-time teachers; hence, they may not have adequate time or opportunity to put the CEFR into practice. The findings are partially in line with a study by Yüce & Mirici (2019), who indicated that insufficient hours affected the unsuccessful implementation of CEFR in class. Therefore, these results also indicate that student teachers require additional CEFR training in the area of using reference level descriptions.…”
Section: Findings and Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, as previously mentioned, the participants were not full-time teachers; hence, they may not have adequate time or opportunity to put the CEFR into practice. The findings are partially in line with a study by Yüce & Mirici (2019), who indicated that insufficient hours affected the unsuccessful implementation of CEFR in class. Therefore, these results also indicate that student teachers require additional CEFR training in the area of using reference level descriptions.…”
Section: Findings and Discussionsupporting
confidence: 89%
“…The data showed that the CEFR descriptions were not suited to the 9th grade EFL program. Besides, the results revealed that insufficient hours affected the unsuccessful implementation of CEFR in class (Yüce & Mirici, 2019), which results are consistent with a study by Alih, Yusoff & Abdul (2020), who found that the teachers lacked sufficient support to implement the CEFR in English classrooms.…”
Section: Literature Reviewsupporting
confidence: 90%
See 1 more Smart Citation
“…Lastly, Yuce and Mirici (2019) investigated the 9th grade Efl program using CEFR proficiency descriptors. In this qualitative research, it is found out that the program is compatible with the CEFR descriptors while it is stated that teachers faced problems because of the materials and the class hours.…”
Section: Resultsmentioning
confidence: 99%
“…lected from the open-ended questionnaires. Another concerning aspect raised by the respondents from their study were theoretical content and applicability in which is believed to have excessively influence on non-European language classes offered at the university (Yüce & Mirici, 2019).…”
Section: Cefr In Malaysia and Other Researches Related To The Implementation Of Cefrmentioning
confidence: 99%